New treatment options for lower respiratory tract infections. (2nd September 2017) - Kocsis, Bela; Szabo, Dora
ABSTRACT: Introduction : Community-acquired pneumonia (CAP) and acute exacerbation of chronic obstructive pulmonary disease (AECOPD) are among the most frequent lower respiratory tract infections (LRTIs). They represent an increased morbidity and mortality rate in adults. Areas covered : This review describes recent advances regarding solithromycin, zabofloxacin and delafoxacin antibacterial agents that have been recently developed for treatment of CAP and in AECOPD. All of them have been introduced into phase III clinical trials. We will be summarising chemical structures, pharmacokinetics, antibacterial efficacy and toxicity of these agents. The manuscript has been prepared based on available scientific publications. Expert opinion : Novel agents of known antimicrobial classes have been developed that demonstrate treatment options in CAP and in AECOPD. Antimicrobials discussed in this review showed bactericide effect against major respiratory tract pathogens. Each has multiple targets in bacteria, thus enabling them for more potency, even against strains exhibiting resistance to commonly used antibiotics. Solithromycin, delafloxacin and zabofloxcian demonstrate broad-spectrum antibacterial activity together with other beneficial features like intracellular accumulation, anti-inflammatory effect and inhibition of biofilm production. These agents showed moderately severe or mild adverse events and demonstrated favourable tissue penetration. These features can make solithromycin, zabofloxacin and delafloxacin treatment options in LRTIs.